TEKNIK SUPERVISI PENDIDIKAN ISLAM DI MADRASAH IBTIDAIYAH DARUL ULUM BANGKUANG - ZAKIRURAHMAN ZAKIRURAHMAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The basic objective of this research is to see how the implementation of managerial supervision of educators and education staff and how much influence managerial supervision has on the performance of educators and education staff at Madrasah Ibtidaiyah (MI) Darul Ulum, Bangkuang Village, Karau Kuala District, District South Barito. This research is a qualitative research with a descriptive approach. The resulting data is descriptive in the form of words, expressions and opinions from research subjects orally and filling out supervision questionnaires. Sources of data in this study were 5 (five) respondents who were Madsarasah Heads, BOS Treasurers, Committee Chairs, senior teachers and operators / TU. Supervision techniques are carried out individually, namely interviews with each respondent and filling out supervision questionnaires to assess aspects of managerial supervision. The results of the study show that the implementation of managerial supervision at MI Darul Ulum Bangkuang village includes roles, implementation, evaluation, dissemination of supervision results, follow-up of supervision results and benefits of supervision results. Supervision activities at MI Darul Ulum are included in the